Escherichia coli‐associated granulomatous colitis in dogs treated according to antimicrobial susceptibility profiling. (15th December 2020) - Manchester, Alison C.; Dogan, Belgin; Guo, Yongli; Simpson, Kenneth W.
Abstract: Background: Eradication of intramucosal Escherichia coli correlates with remission of periodic acid‐Schiff‐positive E coli ‐associated granulomatous colitis (GC). Treatment failures attributed to multidrug resistant (MDR) bacteria necessitate alternative approaches. Hypothesis/objectives: Determine clinical outcome of E coli ‐associated GC in dogs treated based on antimicrobial susceptibility profiling and characterize E coli phylogeny and resistance mechanisms. Animals: Twenty Boxers and 4 French Bulldogs with E coli ‐associated GC. Methods: Culture, antimicrobial susceptibility profiling, and molecular characterization of E coli were performed and response to treatment was evaluated. Results: Initial biopsy sample culture yielded fluoroquinolone‐sensitive (FQ‐S) E coli from 9/24 dogs and fluoroquinolone‐resistant (FQ‐R) E coli from 15/24. All but 1 FQ‐R E coli were MDR with susceptibility to macrophage‐penetrating antimicrobials restricted to carbapenems in 13/15 dogs. Of 22/24 treated based on susceptibility profiling, 8/9 FQ‐S dogs had complete initial clinical response (CR) during fluoroquinolone (FQ) treatment, whereas 9/13 FQ‐R dogs had complete or partial response (PR) during meropenem or doxycycline treatment. In 5/9 FQ‐S and 12/13 FQ‐R dogs with follow‐up ≥3 months, CR was sustained in 5/5 FQ‐S (median, 25 months; range, 4‐46) whereas 6/12 FQ‐R had long‐term CR (median, 59 months; range 15‐102), 4/12 PR (median, 19 months; range, 5‐65), and 2/12 had no response (NR). Four dogs with long‐term follow‐up died within 4 years of diagnosis, including 2 euthanized for refractory colitis. Escherichia coli were genetically diverse. Fluoroquinolone resistance was associated with mutations in gyrA and parC, with plasmid‐mediated resistance less common. Conclusions and Clinical Importance: Antimicrobial treatment guided by susceptibility profiling was associated with positive long‐term outcomes in >80% of cases. Fluoroquinolone‐resistance was widespread and not clonal. Further study is required to optimize treatment for dogs with MDR E coli ‐associated GC.